Attitudes of Iraqi youth towards Iraqi popular proverbs: A field study in the city of Baghdad - Hussein, Juman (Al-Adab Journal, 2024)
Popular proverbs are a reflective mirror of the culture of peoples. They summarize many events in a few words. They help bring the meaning closer to the soul and fix it in the mind. They also have an important role in preserving the identity of society as they represent the long human heritage. They are also a repository of social customs and traditions. They carry... Summary of social experiences. It also summarizes many human experiences and presents them to others in ready-made sentences so that they can take a lesson from them. This is why the importance of popular proverbs is no less than the importance of cultural heritage. This analytical descriptive study, in which we relied on the social survey method, was conducted using the sample across several sections, and one of its most important results was that there is a large degree of agreement between the three educational levels in their belief in popular proverbs, as the majority of them tend to believe in them.